Media Picture and Picture dan Pengaruhnya pada Hasil Pembelajaran Sastra - Ma'ruf, Amar (Kajian Bahasa dan Sastra (KABASTRA), 2021)
Indonesian Learning in schools will not be separated from learning literature as one part of the material that must be mastered by students. Not only understanding and mastery of theory, but students must also be able to apply literary learning theory in the form of real works. This relates to the competence of skills that must also be mastered by students as a form and proof of learning outcomes that have been carried out. The use of lecture media, or limited to discussion, is something that students always find and do by teachers. Although some teachers have started to apply several different and creative learning models. This is certainly evidence of the development of learning, considering the current conditions and circumstances require teachers to leave the conventional way and switch to a more modern learning model and a practical way and actually produce learning outcomes not just grades and intelligence in the form of numbers.